Case Report: Extrarenal TFE3 fusion-related renal cell carcinoma - Yang, Zhouliang; Li, Ting; Lv, Kejun; Zhang, Xiaowei (Frontiers in Oncology, 2025)
IntroductionTranscription factor binding to IGHM enhancer 3 (TFE3) fusion-related renal cell carcinoma (TFE3-RCC) is a rare subtype of RCC. Its pathogenesis is primarily associated with chromosomal translocations resulting in TFE3 fusions. TFE3-RCC is most commonly observed in adolescents and young adults, with a higher incidence in women than in men. Typically, TFE3-RCC initially presents as painless hematuria, an abdominal mass, or with systemic symptoms. In recent years, with advancements in molecular diagnostic techniques, the diagnosis rate of TFE3-RCC has increased. However, extrarenal occurrences of TFE3-RCC remain rare. PRCC can fuse with TFE3 causing PRCC-TFE3 fusion-related RCC, a unique subtype of TFE3-RCC.Case presentationWe report a case of PRCC-TFE3 RCC in a 29-year-old woman who was hospitalized owing to a mass in her upper abdomen. To our knowledge, this is the second reported instance of an extrarenal occurrence. Imaging revealed a large mass in the left retroperitoneum, and postoperative pathology revealed that the tumor cells were either epithelioid- or spindle-shaped, with large nuclei, prominent nucleoli, and abundant chromatin. The cells were densely arranged in nests or sheets, with abundant eosinophilic or amphophilic cytoplasm. Immunohistochemical analysis revealed diffuse and strong nuclear positivity for TFE3 but negativity for carbonic anhydrase IX (CAIX). Fluorescence in situ hybridization did not detect a TFE3 break, but RNA sequencing confirmed the presence of a PRCC-TFE3 fusion.ConclusionThe diagnosis of TFE3-RCC requires a comprehensive evaluation of histological features, immunohistochemical markers, and molecular testing. PRCC-TFE3 RCC is highly aggressive with a high recurrence rate and poor prognosis in adults. Surgical resection is the primary treatment for localized lesions. However, close follow-up is necessary owing to a high risk of recurrence and metastasis. Targeted therapies and immunotherapies are potential treatment options for patients with advanced or metastatic disease.